Problem Perceived in Residential House Regarding Air Cooled Split Unit Air-Conditioning - Shey, Qian Wen; Mohd Syafiq Syazwan Mustafa,; Mohammad Ashraf Abdul Rahman, (Progress in Engineering Application and Technology, 2023)
There are many ways to do the troubleshooting on the internet but there is not have standard just for air-cooled split unit air conditioning in Malaysia. The objective of this study is to determine the problem of the ACSU system in the residential area, to analyse the step of maintenance work according to the possible cause for the problem of the air-cooled split unit (ACSU) air conditioners in the residential area and to evaluate the importance of steps for maintenance work according to the possible cause for the problem of the air-cooled split unit (ACSU) air conditioners in the residential area. The methods which were used in this research were the questionnaire, the pilot testing, snowball sampling method and RII analysis method. The authors show the rank of the possible cause for the problem and the rank of the maintenances work step according to the possible cause. This study will bring benefits or be a good guide to the people that perform repairing or maintenance of the air-cooled split unit air conditioning in the residential area especially the rookie in this sector. For further work based on this study, it need to replicate this study in more expert, to get the population of the expert and to replicate this study in more type of the HVAC system.